Novel design concept of micro gas turbine for unmanned aerial vehicles (UAVs) - Huang, Guo Quan (2015)
In recent years, micro gas turbine (MGT) has been a topic of interest among researchers and developers. MGT are well known for their large power density, and the design and implementation are similar to that of a turbocharger. Nonetheless, the use of MGT as a powerplant has its limitations, specifically in aerospace applications, where thermal management within the system is a cause of concern. It is vital to recognise the importance of thermal management in MGT since there is a direct inverse relationship with the thermal efficiency of MGT, which is worth studying. With reference to existing literature and research, there is a lack of information on existing MGT cycle in NTU and sensitive heat transfer analysis. Hence, this paper aims to develop an MGT engine cycle, produce preliminary components of the engine before validating them. A numerical conjugate heat transfer (CHT) will be conducted to investigate any potential option for better thermal management. From the CHT, the study shows that the amount of heat transfer through the shaft is considered insignificant and that designing of the bearing housing is the key to better heat management. A shaft length of 30mm would still be sufficient to allow the impeller and radial turbine to have an efficiency of over 70%. The application of steel housing and steel shaft would cause insignificant changes to the efficiencies for 50mm and 100mm shaft length respectively. For the 30mm shaft length, air bearing was found to be lacking to cool the system when compared to conventional lubricating oil. However a 100mm shaft length configuration would allow performance to be the same as the 30mm shaft length with lubricating oil. The usage of lubricating oil would demand more components which eventually outweigh the higher effectiveness for heat removal.